أحكام المسنين في الفقه المالكي – العبادات - - دودي, جهاد (University of Eloued جامعة الوادي, 2017)
يعتبر موضوع أحكام المسنين في باب العبادات من المواضيع التي يجهل أحكامها كثيراً من المسلمين والمسنون خاصة. ويتلخص موضوع البحث في دراسة الأحكام التي تخص المسن في العبادات وذلك في المذهب المالكي,حيث تضمنت تمهيداً يحوي مفهوم المسن, والأعذار التي تصيبه في هاته المرحلة,كالعجز والمرض, وأما المباحث الأخرى تطرقت فيها إلى المسائل التي ترتبط بالمسن في العبادات, فخصصت المبحث الأول للطهارة والصلاة, وقد شمل معظم الأحكام التي تحصل للمسن في طهارته وصلاته كعجزه على الاستنجاء, وصاحب السلس والعاجز عن القيام بأركان الصلاة وغيرها,وخصصتُ المبحث الثاني للمسائل المتعلقة بالزكاة, فتناولتزكاة المال والفطر والنيابة في إخراجها وهل يعتبر المسن من مصارف الزكاة؟والصيام للعاجز عنه والمشقة الحاصلة له, وأنواع العجز, وما يبيح للمسن الفطر, والنيابة في الصيام عنه, وجعلت المبحث الثالث لأحكام الحج وركزت فيه على استطاعة المسن, وقدرته المالية, والبدنية,وأعمال المسن التي يكون فيها عاجزاً والنيابة عنه في بعضها, والحج عنه قبل وفاته, وبعد وفاته, ومسالة الوصية في ذلك, وخاتمة ضمنتها أهم النتائج المتوصل إليها والتوصيات. The topic of the provisions of the elders in the scope of worship is viewed as one of the topics that are not understood by many Muslims and the elder people in particular. The topic of the current study is of the provisions concerning the elderly in worship in the Maliki school (Madhab), which includes a prelude to include the concept of the elder people, and the excuses that afflicts them at this stage, such as helplessness and disease, and the others. The research tackles the issues related to the elder people in worship. As for the other sub-findings dealt with issues related to the elderly in worship. The first topic was devoted to purity and prayer, and it included most of the rulings that were given to the elderly in his purification and prayers, such as his inability to abstain, and the one who is smooth and incapable of performing the pillars of prayer. Zakat on money and charity given before Eid El-fitre, and giving it on behalf of the doer. And fasting for the disabled and hardship, and kinds of disability, and allows the elderly to eat and drink in Ramadan, and the prosecution in fasting on it, and made the third section of the provisions of the Hajj and focused on the ability of the elder people, and financial and physical capacity, and the performance of the elders in which they are incapacitated so that we perform Hajj on behalf of them in some cases, His death, and after his death, the issue of the commandment (Elwasaya) in that, and the conclusion details out the most important findings and recommendations of this research.
مذكرة ماستر تخصص اصول الفقه
Keywords: أحكام المسن – المسن – العجز; The rules of the elderly- The elderly- Disability